Pembelajaran Sintaksis Arab dengan Menggunakan Media Google Meet pada Masa Pandemi Covid-19 - Bashori, Ahmad; Ansori, Mahfud Saiful (Study Program of Arabic Language Teaching, 2021)
The outbreak of Covid-19 has a great impact on changes in the world of education and teaching. The learning model changes from face-to-face models into online learning, including Arabic learning. Arabic learning is required to adapt to the existing situation to continue to lead to the goals to be achieved. This research will explore how the learning process of Arabic syntax uses online media, Google Meet as a form of adaptation to the world conditions that are in a pandemic disaster. This research was carried out using a qualitative descriptive method. The results of this study are 1) The learning objectives of Arabic syntax using Google Meet in the Covid-19 pandemic period is that students can understand Arabic words and texts and express the intentions of Arabic properly and correctly, 2) Learning Arabic syntax uses Google Meet in the Covid-19 pandemic time using collaboration methods, namely the deductive method, communicative methods, and drill methods, and 3) Arabic syntax learning evaluations using Google Meet in the Covid-19 pandemic period collaborated with the Google Form application, besides the content Evaluation leads to the achievement of the objectives of the Arabic Language Learning Standards, 4) The main problems that hinder the achievement of the learning objectives of Arabic syntax are the assumption that Arabic is difficult to learn either independently or with a teacher and the lack of adequate means to access the Google Meet application.